2023
DOI: 10.3389/fpubh.2023.1156840
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on the mental health of Lebanese pharmacists: A national cross-sectional study

Abstract: IntroductionThe COVID-19 pandemic has induced a global mental health crisis with variable consequences. This study aimed to assess the psychological impact of COVID-19 regarding anxiety, insomnia, depression, and response to trauma on pharmacists in Lebanon during COVID-19, and to identify factors contributing to psychological distress.MethodsThis was a cross-sectional study among pharmacists that involved the use of the 7-item Generalized Anxiety Disorder (GAD-7), 7-item Insomnia Severity Index (ISI), Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…Since a similar analysis was not conducted across this sample in the period preceding 2020 with both the pandemic and the multiple-aspect Lebanese crises, it remains difficult to confer, from the present results, whether these factors have attenuated stress in the study's population, like other previous studies have shown (Voltmer et al, 2021;von Keyserlingk et al, 2022). In fact, this points out the lack of similar studies among Lebanese pharmacy faculty and highlights the need to address such a research gap, although stress levels among the Lebanese population (Younes et al, 2022b) and among Lebanese pharmacy students (Hammoudi Halat et al, 2022;Safwan et al, 2023), have been already…”
Section: Discussioncontrasting
confidence: 65%
“…Since a similar analysis was not conducted across this sample in the period preceding 2020 with both the pandemic and the multiple-aspect Lebanese crises, it remains difficult to confer, from the present results, whether these factors have attenuated stress in the study's population, like other previous studies have shown (Voltmer et al, 2021;von Keyserlingk et al, 2022). In fact, this points out the lack of similar studies among Lebanese pharmacy faculty and highlights the need to address such a research gap, although stress levels among the Lebanese population (Younes et al, 2022b) and among Lebanese pharmacy students (Hammoudi Halat et al, 2022;Safwan et al, 2023), have been already…”
Section: Discussioncontrasting
confidence: 65%
“…Pharmacy graduates are expected to have adequate knowledge and experiences on frequently encountered community conditions [ 33 – 39 ]. They are also expected to demonstrate professional skills to promote the public health [ 40 44 ]. The necessitates a comprehensive pharmacy curriculum with innovative practice experiences [ 45 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the expanded efforts in exploring mental health among university students [ 157 , 158 , 159 , 160 , 161 ] and some workforce categories, especially healthcare personnel [ 162 , 163 , 164 , 165 ], the literature addressing mental health in university faculty remains limited. In the following sections, a summary of the principle mental health issues of faculty, namely anxiety, depression, stress, and burnout, is presented.…”
Section: Review Of the Literature Addressing Mental Health In Academicsmentioning
confidence: 99%